The great leap forward: The political economy of education in Brazil, 1889-1930 - André Martínez Fritscher; Aldo Musacchio; Martina Viarengo (Banco de México, 2010)
Recent research links the inequality across countries and regions to colonial institutions. This paper argues that trade shocks could alter the development path of a country or subnational units, in spite of its colonial institutions. This hypothesis is analyzed using state-level data for Brazil, a country with high regional heterogeneity in endowments. We find that positive trade shocks, or improvements in export tax revenues, increased expenditures on education per capita and education outcomes in the period 1889 to 1930. In fact, trade shocks ended up altering the inequality in education levels across states in a permanent way. The paper ends by explaining why politicians spent windfall tax revenues to invest on education.
Keywords: I20; H41; H75; N26; N36; N46; N96; 330; Institutions; Fiscal Federalism; Education; Long Run Development; Analphabetismus; Bildungspolitik; Bildungsfinanzierung; Bildungsökonomik; Brasilien